Iron-catalyzed directed C2-alkylation and C2-alkenylation of indole via C–H bond activation - Wong, Mun Yee (2016)
Over the past decades, transition metal-catalyzed directed C–H bond functionalization has been developed as a highly effective method to resolve regioselectivity issues in the field of organic synthesis. Recently, a variety of low-valent transition metal complexes have played an important role to promote directed hydroarylation or hydroheteroarylation of unsaturated hydrocarbon molecules. In general, iron is known as one of the most naturally abundant, inexpensive and environmentally friendly transition metals that could exhibit high reactivity and selectivity under mild reaction conditions. These remarkable features have attracted our attention in exploring and developing hydroarylation reactions through directed C–H bond activation. Following a general outline (Chapter 1) of the recent advances in directed hydroarylation and hydroheteroarylation reactions as well as iron-mediated reactions, Chapter 2 details the discovery and development of iron-catalyzed directed C2-alkylation of indole with vinylarenes. The reaction afforded 1,1-diarylalkane derivatives in good yields with exclusive regioselectivity. Next, Chapter 3 describes iron-catalyzed C2-alkenylation of indole with internal alkynes via directed C–H bond activation. The reaction proceeded under mild conditions to afford C2-alkenylated products in good yields with high syn-stereoselectivity. Lastly, Chapter 4 is a concluding chapter that summarizes this thesis research.